Study of quarantine plant diseases in Georgia - Meparishvili, G.; Gorgiladze, L.; Sikharulidze, Z.; Meparishvili, S.; Muradashvili, M.; Ghoghoberidze, S. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
Our Organization has been conducting plant diseases monitoring and diagnostics of their causal agents. We found the following quarantine pathogens: Dickeya sp., Ralstonia solanacearum, Erwinia amylovora, Pseudomonas syringae pv. actinidiae, Synchytrium endobioticum. To fix diseases on time and study their causing pathogens, is fundamental for the country safety and makes it possible not to infect a huge territory.